2021
DOI: 10.26529/cepsj.1191
|View full text |Cite
|
Sign up to set email alerts
|

Modern Aspects of Home Economics Education and Slovenia

Abstract: Home economics operates in the academic, curriculum and social realms, as well as in everyday life. Due to its multidisciplinarity, it includes and interconnects the contents of different disciplines (e.g., healthy lifestyle, nutrition, dietetics, textiles, home, family, consumption, personal and family economics, design and technology), which are considered in terms of meeting the needs of the individual, family, and society. Home economics education and literacy play an important role in acquiring knowledge … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The image that Home Economics in Japan is an activity for women has not been completely eradicated (Branlat & Sano, 2021). In Hong Kong, Erjavsek (2021) points out that Home Economics contents are mainly intended for girls and not boys. Due to prevailing negative attitudes of teachers, parents, peers and patriarchal community, boys chose not to attend Home Economics classes.…”
Section: Gender and Home Science Educationmentioning
confidence: 99%
“…The image that Home Economics in Japan is an activity for women has not been completely eradicated (Branlat & Sano, 2021). In Hong Kong, Erjavsek (2021) points out that Home Economics contents are mainly intended for girls and not boys. Due to prevailing negative attitudes of teachers, parents, peers and patriarchal community, boys chose not to attend Home Economics classes.…”
Section: Gender and Home Science Educationmentioning
confidence: 99%
“…According to Erjavsek (2021), the importance of Home Economics to the family, cannot be overemphasized. It interconnects disciplines to improve the lifestyle, nutrition, dietetics and general lifestyle pattern of the family.…”
Section: Strategies To Become a Lifelong Learnermentioning
confidence: 99%
“…It integrates people's daily practical tools, determined by cultural and societal changes, such as globalization, localization, and technological advances, which are considered difficult to standardize and seen as having a lower economic value towards society [15]. However, research indicates that the central role and curriculum of home economics should aim at promoting sustainable well-being on a personal and global level, which includes health-related self-care techniques, selfperception, self-confidence, positive quality of life [16], and mental-health well-being [17,18]. Through the emphasis on practical skills related to food and textile production, as well as its emphasis on critical thinking and problem solving, a teacher survey has also revealed that home economics education provides a good understanding of household and society sustainable development [18].…”
Section: Introductionmentioning
confidence: 99%